Stem Cell Therapy in Esophageal Disorders - Puspa Zuleika; Legiran Legiran (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Disorders of the esophagus could include various conditions such as inflammation, stricture or esophageal-phase dysphagia. Management of these disorders is rapidly developing, which includes conservative, surgical and modern techniques such as the use of stem cells. Stem cells are characterized as cells which have not differentiated, able to multiply and differentiate into multiple organ cells, and has the ability of self-renewal which is vital in disease management. Mesenchymal stem cells or MSCs are mature stem cells with multidirectional differentiation and also has the ability of self -renewal. It includes adipose MSCs (AMSCs), bone marrow MSCs (BMSCs), umbilical cord MSCs (UC-MSCs) and gingival MSCs. Based on the characteristics of stem cells as well as the anatomy and physiology of the esophagus, stem cells may have a role in the management of esophageal disorders.